Data Mining and Warehousing Approaches on School Smart System: A Conceptual Framework - Janson Luke Ong Wai, Kit; Subarmaniam, Kannan; Vijanth S., Asirvadam (2008)
Data warehouse is a database with tools that stores current and historical data of potential interest. One of them which, will be investigated in this paper, is the state school data. Mining or analyzing data extract from such system would be interesting for possible smart school application. This paper looks at the framework of virtual smart school implementation based on students' exam results.